A Study About The Meaning Of Traditional Food Services In Baralek Events At The Bride's Residence - Zahira, Viona; Yelfi, Reno (Jurnal Pendidikan Tata Boga dan Teknologi, 2022)
This study aims to describe the process of implementing the baralek event in Nagari Muaro, Sijunjung Regency, the food served during the baralek event, the tools used in serving food and the meaning contained in the presentation of food during the baralek event in Nagari Muaro, Sijunjung Regency. The research method used in this study is a qualitative research method with a descriptive approach, namely research that reveals the object of research thoroughly, broadly and deeply. This research was conducted in Nagari Muaro from August to September, the data obtained from the wali nagari, niniak mamak, bundo kanduang, the head of KAN and the community. This research data obtained through interviews, observations and observations as well as documentation. The results of the research on a series of baralek events in Nagari Muaro Kab.Sijunjung, the food served, the tools used and the meaning of the food served. The series of events carried out at the Baralek event in Nagari Muaro, Sijunjung Regency, which consisted of: Ambun Selusur, Asking Mamak's Permission, Monti Jo Siriah Gadang, Pamboli Meal, Alek Bagurau Sumando, Bainai Night, Manjamu Mamak, Mahanda Kokek, Marriage Contract, Bakawan Night. The food served in the baralek event is banana fried kotan, kokek, and goat curry rice. The tools used in serving food at the baralek event are piriang dinner, piriang samba, cambuang, galeh, teapot and tamala. The meaning of the food served is kokek and fried sticky rice which have a close meaning between 4 jini and their parents, while the goat curry rice has the meaning of alek jo niniak mamak.